Multisite catalyst mediated polymer nanostructure formation and self-reinforced polyethylene reactor blends with improved toughness/stiffness balance. (12th October 2016) - Stürzel, Markus; Kurek, Alexander Gerhard; Hees, Timo; Thomann, Yi; Blattmann, Hannes; Mülhaupt, Rolf
Abstract: The design of supported two- and three-site catalysts for ethylene polymerization and tailoring nanophase-separated polyethylene reactor blends represents the key to the development of advanced all-polyethylene nanocomposite materials exhibiting substantially improved performance and high resource-, eco- and energy efficiency. Two or three different single-site catalysts independently produce high density polyethylene (HDPE), ultrahigh molecular weight polyethylene (UHMWPE) and PE wax on the same catalyst support. Since this catalyst-mediated nanophase separation prevents UHMWPE entanglement, typical for conventional homogeneous reactor blends, much higher UHMWPE content up to 30 wt % is incorporated in the presence of PE wax without impairing injection molding. During melt processing the shear-induced oriented UHMWPE crystallization affords shish-kebab-fiber-like nanostructures. This accounts for effective PE self-reinforcement paralleled by simultaneous improvement of stiffness, strength and toughness. Hence, this strategy holds great promise for converting commodity PE into high performance plastics and single component PE composites, entering the performance range currently claimed by glass fiber reinforced PE. Graphical abstract: All-polyethylene nanocomposites are tailored by three-site catalysts mediated nanostructure formation to obtain self-reinforced polyethylene materials. Unlike state-of-the-art polyolefin nanocomposites, requiring either tedious alien nanoparticle dispersion or lamination of drawn polyolefin fibers and tapes, these polyethylene reactor blends exhibit an unprecedented toughness/stiffness balance by shear-induced oriented polyethylene crystallization during injection molding with ultrahigh molecular weight polyethylene contents up to 30 wt %. Highlights: Three single-site catalysts produce trimodal PE on the same catalyst support. The catalyst-mediated nanophase separation prevents UHMWPE entanglement. PE wax enables injection molding of reactor blends with high UHMWPE content. Shish-kebab-fiber-like nanostructures account for effective PE self-reinforcement. This strategy concerts commodity PE into high performance plastics.